Data in the Time of COVID-19: How Data Library Professionals Helped Combat the Pandemic - Cooper, Alexandra; Hill, Elizabeth; Keys, Sandra; Steeleworthy, Michael; Thompson, Kristi (Partnership)

(untitled) (The Partnership: The Provincial and Territorial Library Associations of Canada, 2021)
As the world struggled to respond to the COVID-19 pandemic, researchers worked around the clock to understand what was going on, medically, socially, and economically. At the same time, usual research processes were disrupted: campuses were closed and normal government data collection and dissemination went haywire. Data professionals in academic libraries sprang into action to help. They shared resources, developed workshops, helped find alternative methods of carrying out research, and found ways of coping with the influx of COVID-related data. Social crises are fought on the front lines by medical professionals and service providers, but they are also fought with research, with information, with data. Libraries are at the nexus of information and communication and library professionals were able to play an important supporting role in helping researchers combat the effects of the pandemic.